Oxidation behavior of binary Ti-xW (0 ≤ x ≤ 30, wt%) alloys at 650 °C as a function of W concentration. (October 2016) - Samimi, P.; Collins, P.C.
Highlights: A combinatorial approach was employed to study the oxidation of Ti–W system. Microstructural evolution of the base metal in Ti-W system are comparable to those of the Ti-Mo system. The scale thickness decreases with increase in W content and internal oxidation takes place for very high W concentrations. Abstract: The role of composition on the oxidation behavior of the Ti-W system at 650 °C was investigated utilizing a compositionally graded specimen, Ti-xW (0 ≤ x ≤ 30, all compositions in wt%). Microstructural evolution of the base material and thickness of the oxide layers were assessed as a function of composition. Some of the observations with regard to the evolved base metal microstructure, including: α lath and β rib/precipitates and lamellar structure, were found to be comparable to what is reported for Ti-Mo system. It was also shown that formation of a thinner oxide does not necessarily imply on the lower oxygen ingress.